Hidden Hunger Gender and the Politics of Smarter Foods - Kimura, Aya Hirata (Cornell University Press, 2013)
For decades, NGOs targeting world hunger focused on ensuring that adequate quantities of food were being sent to those in need. In the 1990s, the international food policy community turned its focus to the "hidden hunger" of micronutrient deficiencies, a problem that resulted in two scientific solutions: fortification, the addition of nutrients to processed foods, and biofortification, the modification of crops to produce more nutritious yields. This hidden hunger was presented as a scientific problem to be solved by "experts" and scientifically engineered smart foods rather than through local knowledge, which was deemed unscientific and, hence, irrelevant. In Hidden Hunger, Aya Hirata Kimura explores this recent emphasis on micronutrients and smart foods within the international development community and, in particular, how the voices of women were silenced despite their expertise in food purchasing and preparation.